Fortalecimiento de las capacidades locales a tráves de la educación ambiental para planes de reforestación en la microcuenca del río Membrillo - Andrade Cedeño, Wendy Ximena (2013)
This work was developed with the objective of characterizing the human and natural capital in the Membrillo river watershed and analyzes the relations with life strategies being used. The methodology for the analysis of variables and indicators approached is based on the capital of the communities, which assigns the same importance to each of the indicators for the creation of wellbeing. The results show in the classifying families in three groups of households, which differ in the use of human and natural capital, and related to their life strategies. Group two has greater availability of capitals; it is evident that the human is the factor that determines the quantity and quality of labor available. In group one, two capitals are less fortified, human capital which interacts negatively with natural capital relating them to livelihood, education, training and intervention towards natural resources. Group three is in intermediate situation; its members have a greater variability in learning, highlighting the planting of trees to conserve water and for shade of productive animals. As a result this work provides the urgency of working to strengthen human capital to natural and achieving a sustainable balance in time.